O Espelho de Machado de Assis em língua inglesa: tradução, retraduções e recepção - Silva, Luciana Alves da (2019)
This research aims to analyze one translation and four retranslations of the short story “O espelho”, by Machado de Assis to the English language. The internationalization of the fiction of one of the most famous brazilian writers, who is often compared to great names of the world literature, is not a recent phenomenon, since his novels, short stories and chronicles have been translated and retranslated since the 1920’s in the english-speaking market. An outstanding short story teller, genre in which many scholars believed that he has reached the top of his literary excellency, Machado de Assis published 218 short stories, among which, many have been translated into English.“O espelho” is one of the most analysed short stories of the author, a literary work that contains many characteristics of Machado’s style and some of the most common themes in his fiction, that has been translated and retranslated into English by por W.L. Grossmann & Helen Caldwell (1963), Wilson Loria (1995), John Gledson (2008), John Chasteen (2013), and Margareth Jull Costa & Robin Patterson (2018). In this research, we have a comparative analysis of the five versions released in the anglophone literary context, specially in the American and British editorial market. Considering concepts of retranslation, we discuss the reception of Machado’s work in the reception context, besides examining linguistics and intertextual aspects from the theoretical scheme proposed by Jose Lambert and Henrik Van Gorp (1985), created to a descriptive approach of literary translation.